The Role of Leadership in Improving the Quality of Education at the Roudhotul Mushafiyyah Islamic Boarding School Central Lampung - Dade Wahyudin; Afifuddin Ahmad Robbani; Latri Ida Aini (Journal of Research in Islamic Education, 2023)
The Kyai as a leader in the pesantren has a major role in improving the quality of education in the pesantren, of course without leaving the salaf identity that already exists in the pesantren. The problem in this research is how to improve the quality of education at the Roudhotul Mushafiyyah Islamic Boarding School and the factors that affect the improvement of the quality of education at the Roudhotul Mushafiyyah Islamic Boarding School. The purpose of this study is to describe the role of leadership in improving the quality of education at the Roudhotul Mushafiyyah Islamic Boarding School and the factors that influence the improvement of the quality of education at the Roudhotul Mushafiyyah Islamic Boarding School. This study uses a descriptive qualitative approach, which describes or describes data related to the role of pesantren leadership in improving the quality of education at the Roudhotul Mushafiyyah Islamic Boarding School, Kotagajah District. The subject of this research is the Kiai while the informant in this study is the Asatidz of the Roudhotul Mushafiyah Islamic Boarding School. Data collection techniques using observation techniques, interviews and documentation. The results of this study indicate that the role of pesantren leadership in improving the quality of education in Roudhotul Mushafiyyah Islamic boarding schools is a number of activities carried out by pesantren leaders to improve the quality of education both in input and output. The leadership role of the Roudhotul Mushafiyyah Islamic Boarding School in improving the quality of education plays a role as a leader and innovator without leaving its characteristics as a salaf Islamic boarding school.